KRITIK PUBLIK TERHADAP FILM INNOCENCE OF MOSLEM - Arif Budiman (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2015)
This article aims to highlight the public criticism of the actors who are involved and/or who involve in the issues surrounding the film Innocence of Moslem (IM). Using appraisal theory of Martin and White, this article focuses on the description of the Indonesian public's view of the IM, by comparing public comments on the Internet. Three groups of public comments are used as data sources, the comments on the news that there are three in www.antaranews.com and www.liputan.com. The comments are classified based on the theory appraisal that includes emotional, ethical, and aesthetic. Based on this analysis, it can be concluded that affectively, Indonesian public attitudes towards the IM movie is divided into three types, ie, negative, neutral and positive. Negative attitudes are most prevalent attitude among the public of Indonesia (75%), neutral assessment (12%) and positive ratings (13%). Affect which emerged as a reaction to the IM into the category of "displeasure," the disappointed and angry as the two emotions that fall in the negative category. From the aspect of ethics, attitude in "makes the movie" is considered by the Indonesian public as having broken the law in Indonesia, such as "the act of defiling religion". In addition, the act has violated Islamic law. From an aesthetic aspect, there are two types of appreciation, the first is compositions negative appreciation, and the second is neutral appreciation